Peningkatan Hasil Belajar Model Inkuiri Terbimbing Materi Pertumbuhan dan Perkembangan di SMP Negeri 17 Palembang - Eka Haryati Yuliany (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret, 2021)
The purpose of this study is to see an increase in learning outcomes in the material growth and development in class VIII Junior High School Number 17 Palembang. This research is a quantitative research using quasi-experimental method design (Quasi Experimental). The design of this study used a preliminary test design and a final test. Based on the average value of the final class test using the Guided Inquiry learning model that is 76.90 is greater than the average value of the class using the lecture method that is 63.70. Then the analysis of the results of the t test calculation is obtained (t-count 6.777 while df (free degree) is 57.983, the significance is 0.000. So 6.777> 1.671 means Ha is accepted because the t-value is greater than the t-table value. And the probability is smaller than 0.05 values the significance is 0.05. So it can be concluded that learning using the Guided Inquiry learning model there is an increase in learning outcomes in the growth and development material of VIII grade students of Junior High School Number 17 Palembang.